PENGGUNAAN PROPENSITY SCORE STRATIFICATION-SUPPORT VECTOR MACHINE UNTUK MENGESTIMASI EFEK PERLAKUKAN AKTIVITAS OLAHRAGA PADA PENDERITA DIABETES MELITUS - Ernawati Ernawati; Bambang Widjanarko Otok; Sutikno Sutikno (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2020)
Randomized Controlled Trial (RCT) is not possible to do in observational studies, mainly in health cases, because it is directly related to human life. Actually, good randomization is needed to make the treatment and control groups have no large differences in the observed variables, so it results from unbiased treatment One alternative method that is increasingly used in statistical analysis in the field of health is the Propensity Score (PS). If the propensity score had estimated using the SVM method and divided into groups of strata that have a similar propensity score, it is known as the Propensity Score Stratification (PSS-SVM). The purpose of the PSS-SVM is to balance the observed variables between the treatment group and the control group by dividing them into several strata groups so that a balanced trend is obtained or the propensity score is called balance. This eliminates the influence of the confounding variables and unbalance of the treatment and control groups and obtain an unbiased estimation of the treatment effect. In this Research, the PSS-Method applied in case of disease complication in patients with Diabetes Mellitus Type 2 at the Regional Public Hospital of Pasuruan with respondents who counted 96 patients. The purpose of using PSS-SVM, in this case, is to reduce the confounding effects (sports activity) that influence disease complications. In strata of 4 reduce the largest bias with the percent bias reduction (PBR) is 86.39% with the smallest standard error is 0.103.